Earthquake Disaster Preparedness Profile Among Students in Bantul - Galuh Titisari; Sabar Nurohman; Suyanta Suyanta; Sri Rejeki (Postgraduate, University of Mataram, 2024)
The purpose of this study is to evaluate the level of preparedness of students in facing earthquake disasters in three schools in Bambanglipuro and to provide recommendations for improving student preparedness. This study utilized a quantitative descriptive method involving 124 students as research samples. The research instrument used was an open-ended questionnaire that had been validated by subject matter experts and language experts. The questionnaire consisted of 17 items taken from four parameters of preparedness: attitude (6 items), emergency response planning (5 items), disaster warning systems (1 item), and social mobilization (4 items). The data obtained were analyzed using ANOVA to determine the differences among the three junior high schools. Based on the research findings, it was found that overall, the three schools had similar levels of preparedness, with SMPN 2 Bambanglipuro being classified as